2022
DOI: 10.3390/ma15155099
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gypsum Content on the Long-Term Performance of Lime-Stabilised Soil

Abstract: The role of gypsum level on the long-term strength and expansion of soil stabilised with different lime contents is not well understood. This research, therefore, studied the effect of varying gypsum concentrations of 0, 3, 6, and 9 wt% (equivalent to the sulfate contents of 0, 1.4, 2.8, and 4.2%, respectively) on the performance of sulfate soil stabilised with two lime levels (4 and 6 wt%). This was carried out to establish the threshold level of gypsum/lime (G/L) at which the increase in G/L ratio does not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In fact, expansive clay containing montmorillonite and illite as clay minerals shows a considerable volume change upon small variations in water content considering the environmental changes (Batool et al, 2021;Hamza et al, 2022). Recently, Ebailila et al (2022) have studied the effective role of different gypsum contents on the long-term performance of limestabilized kaolin soil. They have found that the addition of lime to kaolin soil in the absence of gypsum reduced the expansion through both changing of fabric soil and the development of pozzolanic reactions with the curing time.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, expansive clay containing montmorillonite and illite as clay minerals shows a considerable volume change upon small variations in water content considering the environmental changes (Batool et al, 2021;Hamza et al, 2022). Recently, Ebailila et al (2022) have studied the effective role of different gypsum contents on the long-term performance of limestabilized kaolin soil. They have found that the addition of lime to kaolin soil in the absence of gypsum reduced the expansion through both changing of fabric soil and the development of pozzolanic reactions with the curing time.…”
Section: Introductionmentioning
confidence: 99%
“…Bragg's law explains the characterising and measuring the positions of the reflections, crystals and their structures. Studies on the effect of stabilised soil by XRD and SEM have been done for cement-stabilised compacted tills reinforced with steel slag and slaked lime [6], lime-silica fume and lime-ground granulated blast furnace slag [7], calcium carbide residue and flyash in soil stabilisation [8], fly-ash geopolymer [9], geopolymer based on glass powder and calcium carbide [10], fine Ground Tile Waste [11] and industrial By-Products and Biochars [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ebailila et al [32] studied the effective role of different gypsum contents on the long-term performance of lime-stabilized kaolin soil. They found that the addition of lime into the kaolin soil sample in the absence of gypsum increased the strength and reduced the expansion through both changing of fabric soil, and the development of pozzolanic reactions with the curing time.…”
Section: Introductionmentioning
confidence: 99%